DIAGENETIC CONSTRAINTS ON THE USE OF CERIUM ANOMALIES AS PALAEOSEAWATER REDOX PROXIES: AN ISOTOPIC AND REE STUDY OF CAMBRIAN PHOSPHORITES - Shields G.; Stille P. (My University, 2001)
Seawater rare-earth element (REE) distributions show heavy REE enrichment and cerium depletion but these characteristics are only rarely found in ancient, marine authigenic minerals such as carbonate fluorapatite and calcite. This enigma may be due to changing REE distributions in seawater through time or to post-depositional redistribution of REE. Differentiating between these two factors is, however, far from straightforward as their relative importance is likely to vary and evidence is often ambiguous. In this article, we present REE as well as strontium and sulphur isotope data for basal Cambrian phosphorites of South China, which confirm the emerging rule of thumb that granular phosphorites seldom reveal extreme departures from the seawater norm, and tend to undergo, therefore, less diagenetic alteration of REE spectra than skeletal apatites and other phosphate-types. This study reveals stratigraphic trends in Ce anomalies (Ce/Ce*) that could be taken to imply the preservation of a palaeoenvironmental signal. However, further investigation of our data shows that such trends in phosphorites can also be caused by post-depositional alteration, which tends to (1) increase REE contents, (2) reverse Ce depletion, (3) alter Eu anomalies, and (4) concentrate preferentially the middle REE (MREE). Further alteration, which may be due to weathering, has led to HREE depletion, and positive La and Y anomalies (tetrad effect). This is the first study where Ceanom. and phosphate-bound sulphate S-isotope values could be compared for one particular stratigraphic section, which provides us with an additional tool for the interpretation of diagenetic redox conditions. Least altered phosphorites from Meishucun that yield a strongly negative Ceanom. constrain early Cambrian seawater δ34S to about +33‰. We conclude that phosphorite Ceanom. primarily records variations in the local conditions of diagenesis, while outlining some special cases in which diagenetic redox conditions may broadly reflect local bottom-water redox conditions.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская